Allium ramosum L. (Amaryllidaceae), a neglected alien in the European flora and its oldest record from Poland - Seregin, Alexey P.; Korniak, Tadeusz (Phytotaxa, 2013)
Allium ramosum Linnaeus (1753: 296) is a wild relative of A. tuberosum Rottler ex Sprengel (1825: 38), an important crop plant from East Asia (Blattner & Friesen 2006), while A. ramosum sometimes is cultivated as a vegetable in north-eastern China (Choi & Oh 2011). Both species belong to a small section A. sect. Butomissa (Salisbury 1866: 91) Kamelin (1973: 239), which is subordinated to a subgenus of the same name, A. subgen. Butomissa (Salisb.) N.Friesen in Friesen et al. (2006: 22).